APLIKASI DASHBOARD PENENTU PRIORITAS KERJA TEKNISI PT. TELKOMSEL PEKANBARU MENGGUNAKAN FUZZY LOGIC - Erlin, Ali Hamsar, (Jurnal Ipteks Terapan, 2016)
The difficulty of Telkomselâs technician in determining work priorities to fix the problem of Node-B devices has impacted to the declining quality of data services that are accessed by customers. Dashboard application to determine the work priority of technicians at PT. Telkomsel Pekanbaru has been analyzed, designed, and evaluated. This application is built using fuzzy logic tahaniâs model Â with input parameters such as the temperature of devices, age of site maintenance and Â site revenue.Output of this application is the recommendations which is the Node-B devices have to check based on the appropiate of temperature criteria. The results showed that the dashboard application is able to identify high temperature of Node-B devices quickly and accurately, hence the quality of data services is maintained.